Molecular-Level Control of Ciclopirox Olamine Release from Poly(ethylene oxide)-Based Mucoadhesive Buccal Films: Exploration of Structure-Property Relationships with Solid-State NMR - Urbanova, Martina; Gajdošová, Markéta; Steinhart, Miloš; Vetchý, David; Brus, Jiří (Molecular pharmaceutics, 2016)
Mucoadhesive buccal films (MBFs) provide an innovative way to facilitate the efficient site-specific delivery of active compounds while simultaneously separating the lesions from the environment of the oral cavity. The structural diversity of these complex multicomponent and mostly multiphase systems as well as an experimental strategy for their structural characterization at molecular scale with atomic resolution were demonstrated using MBFs of ciclopirox olamine (CPX) in a poly(ethylene oxide) (PEO) matrix as a case study. A detailed description of each component of the CPX/PEO films was followed by an analysis of the relationships between each component and the physicochemical properties of the MBFs. Two distinct MBFs were identified by solid-state NMR spectroscopy: (i) at low API (active pharmaceutical ingredient) loading, a nanoheterogeneous solid solution of CPX molecularly dispersed in an amorphous PEO matrix was created; and (ii) at high API loading, a pseudoco-crystalline system containing CPX-2-aminoethanol nanocrystals incorporated into the interlamellar space of a crystalline PEO matrix was revealed. These structural differences were found to be closely related to the mechanical and physicochemical properties of the prepared MBFs. At low API loading, the polymer chains of PEO provided sufficient quantities of binding sites to stabilize the CPX that was molecularly dispersed in the highly amorphous semiflexible polymer matrix. Consequently, the resulting MBFs were soft, with low tensile strength, plasticity, and swelling index, supporting rapid drug release. At high CPX content, however, the active compounds and the polymer chains simultaneously cocrystallized, leaving the CPX to form nanocrystals grown directly inside the spherulites of PEO. Interfacial polymer-drug interactions were thus responsible not only for the considerably enhanced plasticity of the system but also for the exclusive crystallization of CPX in the thermodynamically most stable polymorphic form, Form I, which exhibited reduced dissolution kinetics. The bioavailability of CPX olamine formulated as PEO-based MBFs can thus be effectively controlled by inducing the complete dispersion and/or microsegregation and nanocrystallization of CPX olamine in the polymer matrix. Solid-state NMR spectroscopy is an efficient tool for exploring structure-property relationships in these complex pharmaceutical solids.
Keywords: farmaceutická chemie; Ethylene Oxide; krystalizace; ethylenoxid; pyridony; Biological Availability; Nanoparticles; Polyethylene Glycols; Oral Mucosal Absorption; Polymers; biologická dostupnost; Chemistry, Pharmaceutical; adheziva; Mouth Mucosa; Adhesives; Drug Liberation; Pyridones; rozpustnost; Solubility; nanočástice; polyethylenglykoly; magnetická rezonanční spektroskopie; ústní sliznice; orální absorpce; polymery; Crystallization; Magnetic Resonance Spectroscopy; uvolňování léčiv